Local Knowledge and Vegetation Composition of Boli Fruit (Xylocarpus granatum J.Koenig) in Balikpapan Bay, East Kalimantan - Amir Ma'ruf (Journal of Tropical Ethnobiology, 2022)
Boli fruit (Xylocarpus granatum J.Koenig) is one of the mangrove plants used by the Balikpapan Bay surrounding community as sunscreen. The seed part of the Boli fruit is simply processed to make sunscreen powder. Local communities around mangrove forests, especially women who work in gardens or ponds, use this fruit as a cold powder to withstand the heat of the sun which can discolor the skin. The mangrove area is one of the habitats located in Balikpapan Bay. The study aimed to describe the local people knowledge, composition and structure of mangrove vegetation on Balikpapan Bay, East Kalimantan. Vegetation data collection was carried out using the plotted path method (2 paths and 33 plots). Vegetation analysis parameters include relative density, relative frequency, and relative dominance. The results of the study found that there are eight mangrove species consisting of seven clans and five tribes. Xylocarpus granatum species is present at every stage of growth. Mangrove trees are found in a diameter distribution between 10 and 20 cm. Trees with a height of more than 15 m dominated the area.